New data on the late Famennian miospore assemblage of the Cercal Anticline (westernmost Iberian Pyrite Belt area), Portugal - Pereira, Zélia (2008)
The Cercal Anticline (CA) is located in the westernmost region of the Iberian Pyrite Belt (IPB). The exposed stratigraphic sequence includes, in ascending order, the Volcano-Sedimentary Complex (VSC) followed by the Xistos das Abertas Fm, which passes gradually to the flysch sequence of the Mira Formation (Carvalho, 1976).